Large‐Scale Growth and Field‐Effect Transistors Electrical Engineering of Atomic‐Layer SnS2. Issue 46 (7th October 2019) - Xu, Liping; Zhang, Peng; Jiang, Huaning; Wang, Xiang; Chen, Fangfang; Hu, Zhigao; Gong, Yongji; Shang, Liyan; Zhang, Jinzhong; Jiang, Kai; Chu, Junhao
Abstract: 2D layers of metal dichalcogenides are of considerable interest for high‐performance electronic devices for their unique electronic properties and atomically thin geometry. 2D SnS2 nanosheets with a bandgap of ≈2.6 eV have been attracting intensive attention as one potential candidate for modern electrocatalysis, electronic, and/or optoelectronic fields. However, the controllable growth of large‐size and high‐quality SnS2 atomic layers still remains a challenge. Herein, a salt‐assisted chemical vapor deposition method is provided to synthesize atomic‐layer SnS2 with a large crystal size up to 410 µm and good uniformity. Particularly, the as‐fabricated SnS2 nanosheet‐based field‐effect transistors (FETs) show high mobility (2.58 cm 2 V −1 s −1 ) and high on/off ratio (≈10 8 ), which is superior to other reported SnS2 ‐based FETs. Additionally, the effects of temperature on the electrical properties are systematically investigated. It is shown that the scattering mechanism transforms from charged impurities scattering to electron–phonon scattering with the temperature. Moreover, SnS2 can serve as an ideal material for energy storage and catalyst support. The high performance together with controllable growth of SnS2 endow it with great potential for future applications in electrocatalysis, electronics, and optoelectronics. Abstract : Large‐scale (over 410 µm) SnS2 atomic layers, whose field‐effect transistors show a high on/off ratio of 10 8 and carrier mobility of 2.58 cm 2 V –1 s –1, are successfully synthesized by a scalable salt‐assisted chemical vapor deposition method. The effect of temperature on the electrical properties is systematically investigated, suggesting the scattering mechanism transforms from charged impurities scattering to electron–phonon scattering.